Discussing factors associated with quality of life in cancer follow-up appointments: a preliminary test of a pragmatic model for clinical practice. (April 2019) - Lindner, Oana C; McCabe, Martin G; Boele, Florien; Mayes, Andrew; Talmi, Deborah; Radford, John; Wearden, Alison
Objective: The aim of this study is to perform a preliminary test of a practical, evidence-based model to enable discussions around quality of life–related concerns during cancer follow-up appointments. Design: Cross-sectional study measuring quality of life, illness perceptions, emotional distress, fatigue, and subjective cognitive complaints. Setting: Cancer outpatient follow-up clinics in four National Health Services in the United Kingdom. Participants: Working-age post-treatment cancer patients, treated with curative intent. Interventions: Not applicable. Main measures: European Organisation for the Research and Treatment of Cancer – Quality of Life Questionnaire – Core 30, Illness Perceptions Questionnaire – Revised, Hospital Anxiety and Depression Scale, Chalder Fatigue Scale, and Cognitive Failures Questionnaire. Results: Fifty-seven cancer patients, with a mean age of 36 years and on average 2.75 years post treatment, returned the completed questionnaires. Anxiety partially mediated the association between subjective cognitive complaints and illness identity (60%) and timeline (25%). Cognitive complaints mediated the relationships between quality of life and anxiety (45%), depression (30%), and fatigue (62%). Depression mediated the relationships between quality of life and illness identity (48%) and timeline (40%). Conclusion: Our study provides a preliminary test of an evidence-based model to help elicit quality of life–related concerns during cancer follow-up appointments. Illness perceptions are associated with quality of life through the mediation of other cancer-relevant factors. Discussing the type, origin, and expected duration of symptoms may elicit other concerns, such as emotional distress, fatigue, or cognitive complaints, which explained a significant amount of the relationship between illness perceptions and quality of life.